Strategic market management - Aaker, David A. (John Wiley & Sons, Inc., 2005)
"Completely revised and updated, David Aaker's authoritative book approaches strategy development from an external perspective driven by a structured analysis of customers, competitors, market trends, and the broader environment. It shows how to build on strategic analysis to create business strategies that will be relevant and compelling to customers, sustainable to competitive attack, and draw on assets and competencies of the organization. Additional topics such as strategic investment, strategic positioning, growth options, global strategies, and organization building provide guidance to strategists."--Jacket